TRAZAS FOSILES DEL PALEOZOICO SUPERIOR CONTINENTAL ARGENTINO (Ameghiniana, 2013)
Trace fossils from the Upper Paleozoic of Argentina are described and their paleoenvironmental and stratigraphic range, preservation, and origin are discussed. The ichnofossils described herein are: Ancorichnus coronus; Beaconichnus darwinum; cf. Beaconichnus darwinum; Didymaulichnus alternatus; D. lyelli; Gordia marina; Isopodichnus problematicus; Kouphichnium minusculum; Maculichna ichnosp.; Merostomichnites aicuñai; Mirandaichnium famatinense; Orchesteropus atavus; Palaeophycus tubularis; P. striatus; Umfolozia sinuosa and U. cf. U. longula. Two ichnoassemblages have been recognized: Carboniferous deep lacustrine (Didymaulichnus trace fossil assemblage) and Permian fluviolacustrine trace fossil assemblages. The latter is subdivided into three ichnocoenoses: Ancorichnus,Umfolozia and Isopodichnus. The Didymaulichnus trace fossil assemblage characterizes oxygenated deep glacial lakes and mainly consist of arthropod locomotion traces, grazing trails beeing common also. The Ancorichnus ichnocoenosis is present in floodplain deposits from Patquía and is dominated by arthropod feeding structures. The Umfolozia ichnocoenosis characterizes shallow lake deposits from Bordo Atravesado and is dominated by arthropod crawling traces. The Isopodichnus ichnocoenosis is present in shallow ephemeral pond deposits from La Dorada and consists of resting and locomotion traces of arthropods and bivalves. The Ancorichnus ichnocoenoses is considered as an example of the Scoyenia ichnofacies. Similar trace fossils assemblages have been reported from other Upper Paleozoic non-marine deposits of the rest of Gondwana. It is suggested that some forms (Umfolozia. Mirandaichnium, Tasmanadia) represent a similar morphological pattem and could have been produced by a similar arthropod.